Frequency independent sinusoidal suppression using median filters - Kasparis, Takis (My University, 1991)
The authors proposes the use of a modified median filter operating in the frequency domain for the detection and suppression of narrowband signals of sufficient power, without regard to their center frequency, bandwidth, or peak power. This approach performs better than traditional linear filters (such as notch filters), and it offers several other significant advantages over similar techniques that have been used so far. A primary application of the approach is antijamming protection of direct-sequence spread-spectrum systems.
Keywords: Signal processing; Signal detection; Frequency meters; Information theory